Zwitterionic nanogels crosslinked by fluorescent carbon dots for targeted drug delivery and simultaneous bioimaging. (August 2016) - Li, Wenchen; Liu, Qingsheng; Zhang, Peng; Liu, Lingyun
Graphical abstract: Abstract: A zwitterionic multifunctional nanogel drug delivery vehicle was synthesized by copolymerizing ornithine methacrylamide (OrnAA, a newly developed amino acid – derived zwitterionic non-fouling monomer) with fluorescent crosslinkable carbon dots (CCDs). In this construct, the zwitterionic nanogel network served as a functionalizable non-fouling matrix for drug loading, while the introduction of CCDs as crosslinkers enabled the real-time tracking and locating of the nanogel. The nanogels showed exceptional stability when incubated in protein solutions and stable fluorescence similar to that of CCDs. Labeled dextran was encapsulated in nanogels as a model drug, and was released in a controlled manner. Importantly, cellular uptake experiments showed that the folic acid – conjugated nanogels can be specifically internalized by the folate receptor – overexpressed cancer cells, but not in normal tissue cells. This type of multifunctional nanogels holds great potential for targeted delivery and simultaneous imaging in cancer therapy. Statement of Significance: In this work, we developed a zwitterionic multifunctional nanogel drug delivery system, by copolymerizing ornithine methacrylamide (OrnAA, a newly developed amino acid – derived zwitterionic non-fouling monomer) with fluorescent crosslinkable carbon dots (CCDs). The non-fouling pOrnAA network provides the nanogels with great stability in biophysical environments and serves as a matrix for drug loading, whereas the fluorescent CCDs not only serve as crosslinkers but also provide stable (i.e., non-photobleaching) fluorescence signals for real-time tracking of the nanogels in the delivery process. A model drug dextran loaded in the nanogels was shown to be released in a controlled manner. Furthermore, the abundant functional groups possessed by pOrnAA can be further conjugated with ligands for specific cell targeting. Our results show that folic acid-modified nanogels were only selectively internalized in folate receptor overexpressed cancer cells, but not in normal tissue cells. Such multifunctional zwitterionic nanogels hold great potential for targeted drug delivery and simultaneous imaging in cancer therapy, due to their great stability, bioimaging capability, excellent biocompatibility, controlled drug release, and selective cell targeting.